PENGARUH REBUSAN BAYAM MERAH TERHADAP PENINGKATAN KADAR HEMOGLOBIN IBU HAMIL DI KELURAHAN LOSUNG KECAMATAN PADANGSIDIMPUAN SELATAN KOTA PADANGSIDIMPUAN TAHUN 2020: REBUSAN BAYAM MERAH - Dewi, Sri Sartika Sari; Panjaitan, Meliana Nurhayati; Ramadhini, Delfi (Universitas Aufa Royhan, 2021)
Anemia in pregnancy is a major health problem in developing countries with high morbidity rates in pregnant women. The pregnancy rate due to anemia in Asia is estimated at 72.6%. The high prevalence of anemia in pregnant women is a problem currently facing the Indonesian government. Anemia often occurs due to a lack of iron content in food, very low absorption of iron from food, the presence of substances that inhibit iron absorption. Iron anemia in pregnancy is a condition in which the mother with an Hb level below 11 grams / dL in the first and third trimesters and an Hb level less than 10.5 grams / dL in the second trimester of pregnancy. This study aims to determine the effect of red spinach stew on increasing hemoglobin levels in pregnant women in the Losung village, Padangsidimpuan Selatan district. The research method is Quasi Experiment with research design One group pre test post test design. Samples were taken using total sampling. The number of samples was 20 pregnant women. Data analysis using Paired T Test. The results showed P = 0.000 (P <0.05). The conclusion is the effect of red spinach decoction on increasing hemoglobin levels in pregnant women. It is hoped that pregnant women who experience anemia or low Hb during their pregnancy are advised to consume red spinach stew. Key: Red spinach stew, Hemoglobin levels for pregnant women and maintaining dietary nutrition are highly recommended for foods containing iron.